Appreciation of dental aesthetics and psychosocial impact associated with the presence of chromatic and occlusion alterations in young students of health sciences, Lima – 2017 - Romero Flores, Katherine (2018)
Objective. To establish the association between the appreciation and psychosocial impact of dental aesthetics with the presence of chromatic alterations and occlusion in young students of health sciences. Material and methods. The study was prospective, cross-sectional, observational and correlational. The sample size was 326 students from 16 to 28 years of age belonging of the Federico Villarreal National University. The subjective evaluations were measured through the Psychosocial Impact Questionnaire of the dental aesthetics (PIDAQ) and for the appreciation, dental photographs of the previous sector were taken and these were presented on a digital tablet, where the participants rated the aesthetics of the color and position of your teeth by Likert scal. Likewise, alterations in occlusion were evaluated using the Dental Aesthetic Index (DAI) and chromatic alterations, caused by enamel defects, using the Enamel Defects Index (IDDEm). Results. The chromatic characteristics, of irregularity and dental occlusion on the esthetic appreciation, were statistically significant (p<0.01); however, with the characteristics of spacing, not association was found (p=1.00). The PIDAQ increased with the DAI score, showing a very significant positive relationship (p<0.01). The IDDEm with PIDAQ, there was an association (p<0.01) except for the "Social" dimension. Conclusion. Minor irregularities are better accepted; as these are more severe, an unpleasant appreciation increases, generating even a greater psychosocial impact on the quality of life.